A chemical circular communication network at the nanoscale. Issue 4 (15th December 2020) - de Luis, Beatriz; Morellá-Aucejo, Ángela; Llopis-Lorente, Antoni; Godoy-Reyes, Tania M.; Villalonga, Reynaldo; Aznar, Elena; Sancenón, Félix; Martínez-Máñez, Ramón
Abstract : A community of three nanodevices communicates through a hierarchically programmed circular flow of chemical information between members. Abstract : In nature, coordinated communication between different entities enables a group to accomplish sophisticated functionalities that go beyond those carried out by individual agents. The possibility of programming and developing coordinated communication networks at the nanoscale—based on the exchange of chemical messengers—may open new approaches in biomedical and communication areas. Here, a stimulus-responsive circular model of communication between three nanodevices based on enzyme-functionalized Janus Au–mesoporous silica capped nanoparticles is presented. The output in the community of nanoparticles is only observed after a hierarchically programmed flow of chemical information between the members.